Problem of uniqueness of an element of the best nonsymmetric L 1-approximation of continuous functions with values in KB -spaces - Babenko, V. F.; Tkachenko, M. E. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We consider the problem of characterization for subspaces of the uniqueness of element of the best nonsymmetric